Las plantas y la sabiduría popular en la medicina tradicional - Maza Rosales, Celina (2018)
The purpose of education is to train people capable of achieving their ethical, intellectual, artistic, cultural, physical, spiritual and religious development by promoting the formation and consolidation of their identity and self-esteem and their proper and critical integration into society by recognizing medicinal plants._x000D_ The profile of the educator that is intended to be formed is based on the Christian social humanist conception, since it is proposed to create in the students solidarity, participation, critical thinking, free and imaginary expression and creativity in recognition of the treatments of the health of humanity._x000D_ The pedagogical processes and moments of the cavity are fully oriented to form critical, reflective beings in order that their learnings are significant evident in the use of traditional medicinal plants._x000D_ In this work the debate strategy has been used where the student makes use of the oral language encouraging their balanced and respectful participation the means and materials used in the present learning activity allows integral_x000D_ The summary of student learning will allow us to effectively see each student's expression ability in the learning process.